Multimodal Imaging and Analysis of the Neuroanatomical Organization of the Primary Olfactory Inputs in the Brownbanded Bamboo Shark, Chiloscyllium punctatum - Camilieri-Asch, Victoria; Caddy, Harrison T.; Hubbard, Alysia; Rigby, Paul; Doyle, Barry; Shaw, Jeremy A.; Mehnert, Andrew; Partridge, Julian C.; Yopak, Kara E.; Collin, Shaun P. (Frontiers in Neuroanatomy, 2020)
There is currently a limited understanding of the morphological and functional organisation of the olfactory system in cartilaginous fishes, particularly when compared to bony fishes and terrestrial vertebrates. In this fish group, there is a clear paucity of information on the characterization, density, and distribution of olfactory receptor neurons (ORNs) within the sensory olfactory epithelium lining the paired olfactory rosettes, and their functional implications with respect to the hydrodynamics of incurrent water flow into the nares. This imaging study examines the brownbanded bamboo shark Chiloscyllium punctatum (Elasmobranchii) and combines immunohistochemical labelling, using antisera raised against five G-protein α-subunits (Gαs/olf, Gαq/11/14, Gαi-1/2/3, Gαi-3, Gαo) with light and electron (transmission and scanning) microscopy to characterize the morphological ORN types present. Three main ORNs (“long”, microvillous and “crypt-like”) are confirmed and up to three additional microvilli-bearing types are also described; Kappe-like (potential or homologous “Kappe” as in teleosts), pear-shaped and teardrop-shaped cells. These morphotypes will need to be confirmed molecularly in future. High-resolution X-ray diceCT scans of the olfactory rosettes, olfactory bulbs (OBs), peduncles, and telencephalon reveal a lateral segregation of primary olfactory inputs within the OBs, with distinct medial and lateral clusters of glomeruli, suggesting a potential somatotopic organisation. However, most ORN morphotypes are found to be ubiquitously distributed within the medial and lateral regions of the olfactory rosette, with at least three microvilli-bearing ORNs labelled with anti-Gαo found in significantly higher densities in medial lamellae. These microvilli-bearing ORN morphotypes (microvillous, “Kappe-like”, “pear-shaped”, and “teardrop-shaped”) are the most abundant across the olfactory rosette of this species, while ciliated ORNs are less common and crypt cells are rare. Spatial simulations of the fluid dynamics of the incurrent water flow into the nares and within the olfactory cavities indicates that the high densities of microvilli-bearing ORNs located within the medial region of the rosette are important for sampling incoming odorants during swimming and may determine subsequent tracking behaviour.